PSV-32 Pulmonary arterial pressure in cattle influences beef color during retail display. (30th November 2020) - Zhai, Chaoyu; Delmore, Robert J; Geornaras, Ifigenia; Speidel, Scott; Holt, Tim; Thomas, Milt; Enns, Mark; Nair, Mahesh N
Abstract: Pulmonary hypertension is a noninfectious disease of cattle at altitudes > 1524 m (5, 000 ft). Mean pulmonary arterial pressures (mPAP) ≥ 50 mmHg is used as an indicator for pulmonary hypertension in cattle. Meat quality attribute, such as color, critically influencing consumer purchase decision, is economically significant. However, the effect of pulmonary arterial pressures (PAP) on postmortem beef color has not been investigated. To examine this, instrumental color, metmyoglobin reducing activity (MRA), and lipid oxidation of aged strip loins (longissimus lumborum; LL) steaks from high PAP (98±13; n = 5) and low PAP score (41±3; n = 6) fattened Angus steers (i.e., live weight of 600 kg) were evaluated during simulated retail display (day 1, 3, 5, 7, 9). A split-plot design was used to analyze the effects of PAP score and display day on instrumental color, MRA, and lipid oxidation. Data analysis was performed using R with the lme4 package as a mixed model, where PAP score (high or low), display day, and their interactions were the fixed effects, and random effect was individual steer. Differences between least square means (P < 0.05) were determined by Tukey's multiple comparisons. An interaction (P < 0.05) between PAP score and display day for redness (a* value), chroma, hue, and MRA was observed. The LL steaks from high PAP score animal had lower (P < 0.05) redness, chroma, and hue, than from low PAP score steer on day 9. A main effect (P < 0.05) of display day on lipid oxidation of was observed, with lipid oxidation increasing as display days increased. The results of current study indicated that the LL steaks from steers with high PAP score have lower color stability than those from steers with low PAP score during simulated retail display. Research partially supported by USDA-NIFA grant: 2018-67015-28241.